CAPIO-CL: The CAPIO Coordination Language - Santimaria, Marco Edoardo; Martinelli, Alberto Riccardo; Colonnelli, Iacopo; Cantalupo, Barbara; Torquati, Massimo; Aldinucci, Marco (International journal of parallel programming, 2025)
The performance bottleneck in file-based workflows remains a pressing issue in the realm of I/O-based workflows. To address this challenge, a novel annotation language has been developed. CAPIO-CL is positioned as an innovative I/O coordination language, enabling users to annotate data dependencies within file-based workflows with synchronization semantics pertinent to the involved files and directories. Through the information provided by the language, optimization opportunities arise in streaming and preemptive data movement. This paper serves to illustrate the semantics and syntax enabling CAPIO-CL to enhance the performance of in situ workflows without necessitating the rewriting or modification of the original workflow application steps. Finally, an analysis of CAPIO-CL is provided, taking into consideration both language expressiveness and application performance enhancement.